Faktor-Faktor Yang Mempengaruhi Intensi Membeli Produk Wayang Kulit Pada Masyarakat Suku Jawa - Rita Setyani Hadi Sukirno; Hadi Sutarmanto (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2007)
The aim of this research is to identity factors that influences purchase intention of leather puppet in Javanese ethnic. This research discusses all factors which possibly appear in the responden.The subject of this research are buyers who visit Handicraf Hadi Sukirno especially Javanese people. Theoretical sampling was use in the research. The method of this research is observation method and interview method. The observation was done in 9 respondent and the interview was done on 4 respondent. The guide interview was used in this research.Design of this research is collective case study. Analysis technique this research is thematic analysis technique. The basic theory in this research is Ajzen on this result of this research can be concluded that purchase intention of the leather puppet in Javanese people was influence by External Factor and Internal Factor. The Internal Factor consist of subject appreciation to puppet, subject affection and interest to puppet and culture, product (puppet) image, subject knowledge and perception, value and self concept. The external factors consist of social economic and media information influence. Key words : purchasing intention, leather puppet